2016
DOI: 10.1055/s-0042-116441
|View full text |Cite
|
Sign up to set email alerts
|

Role of Probiotics in Managing of Helicobacter Pylori Infection: A Review

Abstract: is a prevalent pathogen which is considered as an etiological cause for gastroduodenal ulcers, and a substantial risk factor for gastric malignancies. The vital factor to take into account is that roughly half of the world's population is infected with this bacterium. However, most subjects colonized remain asymptomatic and do not require any treatment. Several antimicrobial agents such as amoxicillin, clarithromycin and metronidazole are used to eradicate the infection. However, these drug regiments do not er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 61 publications
0
13
0
5
Order By: Relevance
“…The combined use of antibiotics and probiotics has recently been shown to improve the eradication rate for certain infections (Kafshdooz et al, 2017 ). However, there is yet insufficient data to assess the safe use of probiotic bacteria in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The combined use of antibiotics and probiotics has recently been shown to improve the eradication rate for certain infections (Kafshdooz et al, 2017 ). However, there is yet insufficient data to assess the safe use of probiotic bacteria in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The most important characterisics of a microorganism as a probiotic are: the ability to pass through the gastro-intestinal tract, tolerance to low pH and bile salt, auto-aggregation and co-aggregation, hydrophobicity, the presence of the genes encoding adhesion proteins, β-galactosidase production, survival in the presence of commercial drugs, and the absence of the genes encoding virulence factors. Studies indicate that L. Bulgaricus almost has all of the above mentioned characterisics [30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…In theory, prebiotics, probiotics, and symbiotics can reestablish the gut microbiota, competing for nutrients with pathogenic bacteria, inhibiting the activity of toxins, and performing immunomodulatory functions (162) . Experimental animal studies have shown that surface proteins in probiotic strains limit the colonization of the stomach by HP (163) . Strains of Lactobacillus salivarius and L. casei may inhibit HP urease activity (by producing lactic acid) and synthesize cytokines, which are involved in inflammatory processes (164) .…”
Section: Level Of Evidence: 4 Grade Of Recommendation: Cmentioning
confidence: 99%